Variasi Dosis Mulsa Organik Akasia dan Kirinyuh dalam Mengendalikan Gulma pada Tanaman Kedelai : Studi Karakteristik Pertumbuhan Tanaman Kedelai - Ramut, Anuar; Harta, Rika Yusli; Pani, Mario; Sitinjak, Lentina; Mahfirah, Adhaini (AGROSUSTAIN, 2025)
The success of controlling weeds in soybean plantations, apart from being determined by the type, also determines the dose of mulch. This research aims to obtain the type and dosage of organic mulch to control weeds in soybean plantations. The research was carried out from August to December 2024, in Lawe Sagu Hulu Village, Lawe Bulan District, Southeast Aceh Regency, Aceh Province. The types of organic mulch used are: acacia and kirinyuh, and the doses used are: 0; 4.8; 9.6; 14.4 and 19.2 tons ha-1. The design used was a bifactorial randomized block design with 4 replications. The variables observed were: plant height, number of leaves, root wet weight and plant wet weight. The results of the research show that the kirinyuh type of organic mulch can increase plant height during the 20th and 30th daily periods. An organic mulch dose of 14.4 tons ha-1 can increase the height of soybean plants for the 20, 30 and 40 daily periods and increase the wet weight of soybean plants for the 20, 30, 40 and 50 daily periods. A dose of 19.2 tons ha-1 can increase the wet weight of roots for 20 daily periods. There was no interaction between the type and dose of acacia and kirinyuh organic mulch on the observation of soybean plant growth.